Clinical Characteristics and Microorganisms Isolated in Community-Acquired Pneumonia in the COVID-19 Period - Meritxell Gavalda; Maria Isabel Fullana; Adrià Ferre; Rebecca Rowena Peña; Julen Armendariz; Orla Torrallardona; Aina Magraner; Alejandro Lorenzo; Carles García; Gemma Mut; Lluís Planas; Carla Iglesias; et al. (Canadian Journal of Infectious Diseases and Medical Microbiology)
Introduction. Community-acquired pneumonia is a leading cause of mortality and hospital admissions. The aetiology remains unknown in 30–65% of the cases. Molecular tests are available for multiple pathogen detection and are under research to improve the causal diagnosis. Methods. We carried out a prospective study to describe the clinical characteristics and aetiology of community-acquired pneumonia during the COVID-19 pandemic and to assess the diagnostic effectivity of the microbiological tests, including a molecular test of respiratory pathogens (FilmArray™ bioMérieux). Results. From the 1st of February 2021 until the 31st of March 2022, 225 patients were included. Failure in microorganism identification occurred in approximately 70% of patients. Streptococcus pneumoniae was the most common isolate. There were 5 cases of viral pneumonia. The tested FilmArray exhibited a low positivity rate of 7% and mainly aided in the diagnosis of viral coinfections. Conclusions. Despite our extensive diagnostic protocol, there is still a low rate of microorganism identification. We have observed a reduction in influenza and other viral pneumoniae during the COVID-19 pandemic. Having a high NEWS2 score on arrival at the emergency department, an active oncohematological disease or chronic neurological conditions and a positive microbiological test result were related to worse outcomes. Further research is needed to determine the role of molecular tests in the microbiological diagnosis of pneumonia.